An Analysis of Hate Speech on Students Interaction and The Impact on Student Motivation - Ningsi, Fitri; Syahraini, Alfi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The aims of this research are to investigate the types of hate speech on students interaction such as incitement to hatred, expression of insulting and ridicule or slander of person. Then, to investigate the impact of hate speech on students motivation such as it can make the students less of self-confidence, overthinking, become anti-social and isolate them self from their friends and the worst impact is the student become lazy to go to school and feel depressed. This research uses descriptive qualitative method. The technique of data collecting are take the video, interview and questionnaire. There are three videos which are uses as source of data about types of hate speech, those videos show on the students interaction. Interview with two students and an English lecturer which are uses as source of data about the impact of hate speech on students motivation that consist of 16 questions. Questionnaire which are uses as source of data about the impact of hate speech on students motivation that consist of 10 questions. In collecting the data, the researcher transcribe the videos into written data accurately, and classify the data based on data from utterances of the students then put them into appropriate categories. In order the data can be easy to be identify and to be analyze. After all of the data are collected, the researcherl analysis the data and draw the conclusion. The result of this research can be seen as follows there are the impact of hate speech on students motivation, it can make the students less of self-confidence, overthinking, become anti-social and isolate them self from their friends and the worst impact is the student become lazy to go to school and feel depressed.